Whole grains and adiposity: little association among British adults. - Thane, C; Stephen, A; Jebb, SA (2009)
OBJECTIVES: To examine associations of whole-grain intake with body weight and adiposity in two nationally representative samples of British adults. SUBJECTS/METHODS: A total of 2064 adults aged 16-64 years in 1986-1987, 1599 adults aged 19-64 years in 2000-2001. Whole-grain intake (g day(-1) and 16-g amounts) was estimated from consumption of all foods with >or=10, >or=25 or >or=51% whole-grain content, using 7-day weighed dietary records. Body weight, body mass index (BMI) and, in 2000-2001, waist circumference (WC) were measured. BMI and WC were considered as continuous and categorical variables. For each survey, associations of whole-grain intake with body weight and anthropometric indices were examined in men and women separately, before and after adjustment for age, occupational social class, smoking habit, region, season and, in 2000-2001, misreporting. RESULTS: In 1986-1987, whole-grain intake was inversely associated with percentage of men classified using BMI as obese (P=0.008, trend), independent of other factors. However, intake was not associated with body weight or prevalence of overweight. No corresponding associations were observed among women. In 2000-2001, whole-grain intake was not associated with body weight, BMI or WC. CONCLUSIONS: Two national surveys of British adults, with detailed quantitative estimates of whole-grain intake, provide little evidence of an association of whole-grain intake with body weight or measures of adiposity.